Cellular localization of Type I restriction-modification enzymes is family dependent - Holubová, I; Vejsadová, S; Firman, K; Weiserová, M (Biochemical and biophysical research communications, 2004)
Cellular localization of Type I restriction-modification enzymes EcoKI, EcoAI, and EcoR124I-the most frequently studied representatives of IA, IB, and IC families-was analyzed by immunoblotting of subcellular fractions isolated from Escherichia coli strains harboring the corresponding hsd genes. EcoR124I shows characteristics similar to those of EcoKI. The complex enzymes are associated with the cytoplasmic membrane via DNA interaction as documented by the release of the Hsd subunits from the membrane into the soluble fraction following benzonase treatment. HsdR subunits of the membrane-bound enzymes EcoKI and EcoR124I are accessible, though to a different extent, at the external surface of cytoplasmic membrane as shown by trypsinization of intact spheroplasts. EcoAI strongly differs from EcoKI and EcoR124I, since neither benzonase nor trypsin affects its association with the cytoplasmic membrane. Possible reasons for such a different organization are discussed in relation of the control of the restriction-modification activities in vivo.
Keywords: Subcellular Fractions; restrikční enzymy; DNA Restriction Enzymes; subcelulární frakce; restrikční endonukleasy typu I; Deoxyribonucleases, Type I Site-Specific; Escherichia coli